Triboelectric Nanogenerator Based on Fully Enclosed Rolling Spherical Structure for Harvesting Low-Frequency Water Wave Energy - Wang, Xiaofeng; Niu, Simiao; Yin, Yajiang; Yi, Fang; You, Zheng; Wang, Zhong Lin (Advanced energy materials, 2015)
Water waves are increasingly regarded as a promising source for large‐scale energy applications. Triboelectric nanogenerators (TENGs) have been recognized as one of the most promising approaches for harvesting wave energy. This work examines a freestanding, fully enclosed TENG that encloses a rolling ball inside a rocking spherical shell. Through the optimization of materials and structural parameters, a spherical TENG of 6 cm in diameter actuated by water waves can provide a peak current of 1 μA over a wide load range from a short‐circuit condition to 10 GΩ, with an instantaneous output power of up to 10 mW. A multielectrode arrangement is also studied to improve the output of the TENG under random wave motions from all directions. Moreover, at a frequency of 1.43 Hz, the wave‐driven TENG can directly drive tens of LEDs and charge a series of supercapacitors to rated voltage within several hours. The stored energy can power an electronic thermometer for 20 min. This rolling‐structured TENG is extremely lightweight, has a simple structure, and is capable of rocking on or in water to harvest wave energy; it provides an innovative and effective approach toward large‐scale blue energy harvesting of oceans and lakes. A freestanding‐structured, fully enclosed triboelectric nanogenerator is designed with unique advantages for harvesting wave energy. When resonated with water waves, such a triboelectric nanogenerator can light up 70 LEDs instantaneously. Integrated with electric double‐layer supercapacitors, such a system can power a digital thermometer in a duty cycle of 26.5%, showing its potential application in harvesting blue energy.